US Socker (2008)
As the governing body of soccer in all its forms in the United States, U.S. Soccer has helped chart the course for the sport in the USA for more than 90 years. In this time, the Federation`s mission statement has been very simple and very clear: to make soccer, in all its forms, a preeminent sport in the United States and to continue the development of soccer at all recreational and competitive levels.